Administrative Thought in Kurdish Folk Proverbs (Raparin Journal of Humanities (RJH), 2021)
This research aims to understand and find the relationship between administrative thoughts and theory and Kurdish popular traditional proverbs. This is a theoretical and applied research by comparing (32) Kurdish folk or saying examples with some classic (traditional) and modern theories of managerial thought. This includes two different sciences and fields of management and folk literature. The research is divided into three similar sections according to the title of the research, and its first chapter is devoted to administrative thought, schools and administrative theories, the second chapter: is devoted to the concept, specificity and attempts to collect Kurdish proverbs, and the third chapter is devoted to presenting administrative thought in terms of the fundamentals in the folkloric folk proverb in the Kurdish language. The research reached were reflected in the thought of the Kurds' older generations such grandfathers and grandmothers even though it was not applied in reality, because the Kurds, like other people, have an administrative thought that is perfect and mature, especially in the field of specialization, time, planning, leadership and supervision. Finally the study recommended to writers and researchers, one of the most important of which is that this field should be developed and further researched between administrative thought in all its divisions and branches, with all Kurdish proverbs on the one hand, and with all other topics of Kurdish literature such as poetry, prose, novel ... etc. on the other side.